New and little-known species of the genus Lacon Laporte, 1838 (Coleoptera: Elateridae) of China - Prosvirov, Alexander S. (Zootaxa, 2016)
Two new species of the genus Lacon Laporte, 1838 are described from Yunnan province of China: L. diqingensis sp. nov. and L. lijiangensis sp. nov. Lacon salvazai (Fleutiaux, 1918) is recorded for the first time in China. The position of these species within the genus and their geographical distribution are discussed. A preliminary key to the known species of Lacon of mainland China is provided.